2013
DOI: 10.1111/jocd.12019
|View full text |Cite
|
Sign up to set email alerts
|

Dry skin in the winter is related to the ceramide profile in the stratum corneum and can be improved by treatment with a Eucalyptus extract

Abstract: These results suggest that not only the level of CER, but also specific CER species strongly contribute to dry skin relief and products that increase those are useful to improve dry skin conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 24 publications
(31 reference statements)
3
36
0
1
Order By: Relevance
“…It is reported that the ceramide composition, which is catalyzed by several enzymes, strongly correlates with dry skin conditions and skin conductance. 23 Other molecules involved in the maturation of keratinocytes can be candidates that are influenced by blood flow. To clarify the mechanisms underlying skin physiology affected by blood flow functionality, further in vivo and/or in vitro analysis is required.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the ceramide composition, which is catalyzed by several enzymes, strongly correlates with dry skin conditions and skin conductance. 23 Other molecules involved in the maturation of keratinocytes can be candidates that are influenced by blood flow. To clarify the mechanisms underlying skin physiology affected by blood flow functionality, further in vivo and/or in vitro analysis is required.…”
Section: Discussionmentioning
confidence: 99%
“…O teor de água do estrato córneo e lipídios de superfície como ceramidas e colesterol formam um equilíbrio, o que é muito importante para a função e aparência da pele. As bicamadas lipídicas e a água formam uma estrutura de gel cristalino líquido multilamelarintercelular que está envolvida na prevenção da perda de água transepidermal (14) . A barreira normal da pele é o principal aspecto da homeostase e regeneração da pele.…”
Section: Discussionunclassified
“…The water content of the stratum corneum and surface lipids such as ceramides and cholesterol form a balance, which is very important for the function and appearance of the skin. Lipid bilayers and water form an intercellular multilamellar liquid crystalline gel structure that is involved in preventing transepidermal water loss (14) . A normal skin barrier is the main aspect of skin homeostasis and regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Ceramides can combine with water and prevent water decrease in the SC because ceramides have hydrophilic lipid. In recent years, ceramides have been developed for cosmetics, which are responsible for the permeability barrier and water holding functions of the epidermis [7,8].…”
Section: Introductionmentioning
confidence: 99%